Detection of subclinical hemorrhage using electrical impedance: a porcine study. (31st May 2022) - Murphy, Ethan K; Klein, Samuel B; Hamlin, Alexandra; Anderson, Justin E; Minichiello, Joseph M; Lindqwister, Alexander L; Moodie, Karen L; Wanken, Zachary J; Read, Jackson T; Borza, Victor A; Elliott, Jonathan T; Halter, Ryan J; et al.
Abstract: Objective. Analyze the performance of electrical impedance tomography (EIT) in an innovative porcine model of subclinical hemorrhage and investigate associations between EIT and hemodynamic trends. Approach . Twenty-five swine were bled at slow rates to create an extended period of subclinical hemorrhage during which the animal's heart rate (HR) and blood pressure (BP) remained stable from before hemodynamic deterioration, where stable was defined as <15% decrease in BP and <20% increase in HR — i.e. hemorrhages were hidden from standard vital signs of HR and BP . Continuous vital signs, photo-plethysmography, and continuous non-invasive EIT data were recorded and analyzed with the objective of developing an improved means of detecting subclinical hemorrhage— ideally as early as possible . Main results . Best area-under-the-curve (AUC) values from comparing bleed to no-bleed epochs were 0.96 at a 80 ml bleed (∼15.4 min) using an EIT-data-based metric and 0.79 at a 120 ml bleed (∼23.1 min) from invasively measured BP—i.e. the EIT-data-based metric achieved higher AUCs at earlier points compared to standard clinical metrics without requiring image reconstructions . Significance. In this clinically relevant porcine model of subclinical hemorrhage, EIT appears to be superior to standard clinical metrics in early detection of hemorrhage.